GollumFit: An icecube open-source framework for binned-likelihood neutrino telescope analyses - R. Abbasi; M. Ackermann; J. Adams; S.K. Agarwalla; J.A. Aguilar; M. Ahlers; J.M. Alameddine; N.M. Amin; K. Andeen; C. Argüelles; Y. Ashida; S. Athanasiadou; et al. (Computer Physics Communications, 2026)

Buffelgrass (Pennisetum ciliare) invasion is associated with reduced plant diversity and changes in carbon storage in the Sonoran Desert - R. Chelsea Nagy; Emily J. Fusco; Adam L. Mahood; Dylan P. Murphy; Jennifer K. Balch; Kimberly Franklin; Bethany A. Bradley (Journal of Arid Environments, 2026)

Challenges and Opportunities for Strengthening Bottom‐Tow Fisheries Sustainability - Suresh A. Sethi; Robert D. Murphy; Matthew R. Baker; Anita C. Kroska; Haraldur A. Einarsson; Owen S. Hamel; Shelton J. Harley; Pingguo He; James Ianelli; Stan Kotwicki; Robert A. McConnaughey; Chris McGonigle; et al. (Fish and Fisheries, 2026)
Bottom‐tow gear fisheries (trawls and dredges) produce ~24 million mt of harvest annually, representing a globally important animal‐sourced food system. While many are currently sustainably managed, growing concern over the potential for ecosystem impacts from bottom‐tow gears has increased pressure to improve these fisheries. We assembled an international working group of > 30 contributors, including fishing industry participants, managers, non‐governmental ocean conservation organization representatives, and scientists to synthesize obstacles to bottom‐tow fisheries sustainability and to develop expert‐based recommendations to operationalize sustainability advancements moving forward. We identified 30 key gaps impeding bottom‐towed fisheries sustainability spanning 6 core challenge areas including: seafloor disturbance, bycatch and discards, management design and implementation, fishing operations, cross‐sector conflicts, and public perception and communication. We generated 28 priority recommendations to address bottom‐tow fisheries sustainability obstacles with themes including: addressing data gaps, advancing mechanistic understanding and modelling tools, strengthening management processes, and improving knowledge sharing and communication. Cross‐disciplinary and diverse system experience among fisheries and marine ecosystem stakeholders will be critical for operationalizing bottom‐tow fisheries sustainability advancements. As the global human population approaches 10 bn in the next 30 years, ensuring sustainable wild capture fisheries is an imperative for feeding the world. Outputs from this synthesis serve as a resource for fishing and marine ecosystem stakeholders to identify key challenge areas and associated entry points for solutions‐oriented efforts to improve the sustainability of bottom‐tow fisheries.

The Integration of Fire Ecology and Freshwater Ecosystems in North America: Knowledge Gaps and Research Needs - Morgan L. Piczak; Ava J. A. Sergio; Caliyena R. Brown; Waverley S. Birch; Rebecca L. Flitcroft; Meg A. Krawchuk; Colin P. R. McCarter; Jonathan W. Moore; Brendan P. Murphy; Brooke E. Penaluna; Prabha A. Rupasinghe; Victoria Steblaj; et al. (Global Change Biology, 2026)
Wildfires, unplanned fires that start and spread under the influence of weather and fuel composition, are increasing in frequency, duration, and severity across North America. While wildfires are one component of wildland fire, a broader natural process in many ecosystems, their changing behavior poses growing ecological and management challenges. Although wildfire is widely recognized as an important disturbance, empirical research quantifying its impacts on freshwater ecosystems remains limited and fragmented. As a result, our understanding of how wildfire affects imperiled freshwater systems remains underdeveloped. The objective of this review was to synthesize the existing empirical literature and identify key knowledge gaps to guide future research on wildfire–freshwater interactions across both biotic and abiotic components. At the biological scale, uncertainties remain around species‐ and community‐level responses (e.g., direct and indirect effects on biota). Freshwater habitat dimensions should also be the focus of further research, including alterations to physical structure (e.g., vegetation) and physicochemical conditions (e.g., temperature). From a management perspective, critical questions relate to fire‐informed restoration (e.g., specialized techniques, role of managed burns) and strategies for enhancing ecosystem resilience (e.g., identifying relevant indicators, links to watershed health). Understanding how land‐use change (e.g., forestry) and climate change interact to influence wildfire regimes and generate cumulative effects across landscapes is also essential in this new wildfire reality. To advance research and practice, we recommend comprehensive monitoring, standardization of methods and indicators, recognition of the role of cultural and prescribed burns, meaningful knowledge co‐production, and bridging the gap between scientific knowledge and management action.

A Coast-to-Coast Assessment of Cumulative Impacts and Protection Potential in Canadian Marine Conservation Networks - Grace E. P. Murphy; Selina Agbayani; Jocelyn C. Nelson; Emily M. Rubidge; Ryan R. E. Stanley; Cathryn C. Murray; Noreen E. Kelly (Environmental Management, 2026)
The effectiveness of marine conservation networks depends on their ability to manage and safeguard against the many overlapping human activities and stressors influencing marine ecosystems. Cumulative impact mapping (CIM) combines information on the intensity and location of stressors with the spatial extent and vulnerability of marine habitats to generate a single, relative cumulative impact (CI) score. Despite its potential benefits to inform management and conservation efforts, CIM is not commonly incorporated into conservation network planning. Here, we combine published CIMs from the Canadian Atlantic and Pacific bioregions with existing marine conservation areas (MCAs) to compare impacts inside each MCA against regional impacts. We then conduct a scenario analysis to quantify potential reduction in cumulative impacts in two bioregion’s proposed marine conservation networks by modeling the removal of prohibited activities (bottom contact fishing, dredging, disposal at sea) in alignment with the Canadian Marine Protection Standard. Both regions exhibited similar distributions in current CI scores, with approximately half of MCAs scoring significantly above the regional mean, and the other half below. The scenario analysis predicted a 7% mean decrease (range 0–36%) in cumulative impacts across the Scotian Shelf and 2% mean decrease (range 0–17%) across the Northern Shelf networks. We identified 17 MCAs in the Scotian Shelf and 8 in the Northern Shelf as having high protection potential, which can be a valuable decision support tool for conservation planners. We discuss how CIM can be operationalized for conservation network planning and management.

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Soil property controls on plasticiser, antioxidant and UV absorber additive degradation across a global soil gradient - Michaela K. Reay; Martine Graf; Maddy Murphy; Charlie Monkley; Perrine J. Florent; Benjamin I. Collins; Nguyen Van Hien; Tran Minh Tien; Andreia Neves Fernandes; Tapan Adhikari; Samantha Viljoen; Mona Tolba; et al. (Environmental Science and Pollution Research, 2025)
Additives in agricultural plastics can leach into the surrounding soil during use or improper disposal. Their subsequent degradation rates directly regulate whether they persist and accumulate to levels with ecotoxicological effects or are rendered benign. However, which soil properties primarily regulate the degradation of additives remains unclear (e.g. soil carbon, pH, available nutrients, microbial biomass and community structure). We assessed the degradation of the common plastic additives with different functionalities (DEHP (di(2-ethylhexyl) phthalate; plasticiser), 2-hydroxy-4-n-octyloxybenzophenone (benzophenone-12; BP12; UV stabiliser) and AO168 (tris(2,4-di- tert -butylphenyl) phosphite; antioxidant)) in soils under controlled moisture and temperature conditions over 21 days across contrasting agricultural soils from six countries across a global transect (Australia, Brazil, Egypt, India, Vietnam and the UK). DEHP followed zero-order degradation kinetics, with negligible degradation in soils with low microbial biomass. BP12 degraded fastest via first-order degradation kinetics via ether cleavage and hydroxyl loss. The degradation of DEHP and BP12 was correlated with soil microbial biomass and nitrate concentration. BP12 degradation products detected included benzophenone and benzoic acid. DEHP is degraded via β-oxidation of alkyl groups to dibutyl phthalate and diethyl phthalate and through ester hydrolysis to phthalic acid. AO168 degraded via abiotic oxidation and phosphate ester hydrolysis to 2,4-di- tert -butyl-phenol, and degradation was not well correlated with any measured soil variable. Overall, these results show that the components of additive mixtures leached into soils will degrade at different rates due to varying mechanisms and controls exerted by the soil microbial biomass. Plastic additives have differing potentials to persist in agricultural soils globally, with some likely to accumulate to levels that may impact soil function and pose an ecotoxicological threat to soil biota.

The 10/20/30 planting rule aligns with traditional plant diversity metrics across spatial scales - Michael R. Freiburger; Colleen Murphy-Dunning; Danica A. Doroski; P. Mark Ashton; Jacob D.J. Peters (Urban Forestry & Urban Greening, 2025)

Responses of small mammals to prescribed low-intensity fire: Genetic insights from a northern Australian fire experiment - Alexander R. Carey; Georgina Neave; Teigan Cremona; Hugh F. Davies; Brett P. Murphy; Geoffrey J. Cary; Tiwi Rangers; Toby Barton; Sam C. Banks (Biological Conservation, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Otolith and Genomic Data Reveal Temporal Insights Into Stocking Across a Large River Basin in a Mobile, Long‐Lived Australian Freshwater Fish Species - Katherine A. Harrisson; Luciano B. Beheregaray; Christopher M. Bice; Emily J. Booth; Chris J. Brauer; Gavin L. Butler; David Dawson; Olga Dudchenko; Benjamin G. Fanson; Graeme Hackett; Annique Harris; Matthew J. Jones; et al. (Molecular Ecology, 2025)
Freshwater ecosystems and their biota are under increasing pressure from anthropogenic stressors. In response to declining fish stocks, hatchery and stocking programmes are widely implemented as core components of restoration and management strategies, with positive outcomes for some wild populations. Despite this, stocking remains contentious due to potential genetic and ecological risks to wild populations. Monitoring and evaluation of stocking outcomes are critical to ensuring the long‐term sustainability of wild populations, but identification of stocked individuals post‐release remains a key challenge, particularly for mobile species. In this study, we combined otolith (natal origin and age) and genomic data to identify stocked individuals and evaluate the genetic implications of stocking for a culturally and socioeconomically important and mobile freshwater fish, golden perch Macquaria ambigua (family: Percichthyidae), across Australia's Murray–Darling Basin (MDB). We also generated a chromosome‐level genome assembly. Many close kin were detected across the MDB, increasing in prevalence over recent decades and mostly of hatchery origin. Rivers with many close kin were associated with low effective population sizes ( N e

Evaluation of foliar fungicides for Cercospora leaf spot management in table beet in New York - Pratibha Sharma; Sean P. Murphy; Julie R. Kikkert; Sarah J. Pethybridge (Crop Protection, 2025)

The influence of fire and termites on tree hollow development in an Australian tropical savanna - Ellen Rochelmeyer; Brett P. Murphy; Shaun R. Levick; Alyson M. Stobo-Wilson; Anna E. Richards (Forest Ecology and Management, 2025)

Declines in greater bilby (Macrotis lagotis) geographic range and realised niche are best explained by the invasive red fox (Vulpes vulpes) - Hayley M. Geyle; Alys R. Young; Brett P. Murphy; Chris R. Dickman; Christine Schlesinger; Kelly M. Dixon; Harry Moore; Sarah Legge; Jennifer Silcock; Naomi Indigo; Martin Dziminski; Bruce Greatwich; et al. (Biological Conservation, 2025)

Dominance and rarity in tree communities across the globe: Patterns, predictors and threats - Iris Hordijk; Lalasia Bialic‐Murphy; Thomas Lauber; Devin Routh; Lourens Poorter; Malin C. Rivers; Hans ter Steege; Jingjing Liang; Peter B. Reich; Sergio de‐Miguel; Gert‐Jan Nabuurs; Javier G. P. Gamarra; et al. (Global Ecology and Biogeography, 2024)
Aim Ecological and anthropogenic factors shift the abundances of dominant and rare tree species within local forest communities, thus affecting species composition and ecosystem functioning. To inform forest and conservation management it is important to understand the drivers of dominance and rarity in local tree communities. We answer the following research questions: (1) What are the patterns of dominance and rarity in tree communities? (2) Which ecological and anthropogenic factors predict these patterns? And (3) what is the extinction risk of locally dominant and rare tree species? Location Global. Time period 1990–2017. Major taxa studied Trees. Methods We used 1.2 million forest plots and quantified local tree dominance as the relative plot basal area of the single most dominant species and local rarity as the percentage of species that contribute together to the least 10% of plot basal area. We mapped global community dominance and rarity using machine learning models and evaluated the ecological and anthropogenic predictors with linear models. Extinction risk, for example threatened status, of geographically widespread dominant and rare species was evaluated. Results Community dominance and rarity show contrasting latitudinal trends, with boreal forests having high levels of dominance and tropical forests having high levels of rarity. Increasing annual precipitation reduces community dominance, probably because precipitation is related to an increase in tree density and richness. Additionally, stand age is positively related to community dominance, due to stem diameter increase of the most dominant species. Surprisingly, we find that locally dominant and rare species, which are geographically widespread in our data, have an equally high rate of elevated extinction due to declining populations through large‐scale land degradation. Main conclusions By linking patterns and predictors of community dominance and rarity to extinction risk, our results suggest that also widespread species should be considered in large‐scale management and conservation practices.

P19-89 Toxicokinetic and alternative methods to support dog study waiver decision making in pesticide risk assessment: triclopyr as a case study - N. Printemps; P. Deford; J. Domoradzki; M. Himmelstein; R. Mingoia; L. Murphy; M. Corvaro (Toxicology Letters, 2024)

A clear case for dust obscuration of the lunar retroreflectors - Sanchit Sabhlok; James B.R. Battat; Nicholas R. Colmenares; Daniel P. Gonzales; Thomas W. Murphy (Icarus, 2024)

Neurodevelopmental outcomes in children and adults with Fetal Valproate Spectrum Disorder: A contribution from the ConcePTION project - M. Bluett-Duncan; D. Astill; R. Charbak; J. Clayton-Smith; S. Cole; P.A. Cook; J. Cozens; K. Keely; J. Morris; R. Mukherjee; E. Murphy; P. Turnpenny; et al. (Neurotoxicology and Teratology, 2023)

Temporal and spatial evolution of the 2021 eruption in the Tajogaite volcano (Cumbre Vieja rift zone, La Palma, Canary Islands) from geophysical and geodetic parameter analyses - M. B. Benito; G. E. Alvarado; M. Marchamalo; J. G. Rejas; P. Murphy; R. Franco; D. Castro; C. Garcia-Lanchares; J. Sanchez (Natural Hazards, 2023)
The eruption of the Tajogaite volcano in 2021, in the Cumbre Vieja rift zone (La Palma, Canary Islands), is the most recent but also the most damaging and longest-lasting eruption on the island since historical records began. We analyzed geophysical parameters (seismicity, surface deformation, thermal anomalies, and volcanic activity) with the aim of reconstructing the temporal development of the magma plumbing system. The seismic sequence (> 9000 events, mbLg ≤ 5.0) can be grouped into nine distinct phases, which correspond to well-separated spatial clusters and distinct earthquake regimes. A strong premonitory thermal anomaly was calculated on July 2021 in the South of La Palma. The source of the magma was within the upper mantle (40–20 km depth). A second magma budget (< 15 km depth) indicated a short-term stagnation of alkaline magma within the lower crust, near the Moho. The outline of these earthquakes delineates the magma pathway. Just before and immediately after the eruption (phases 2 and 3), the high-frequency seismicity in the mantle disappeared completely, reappearing ten days after the eruption started. The pattern of deformation began before the eruption with a breakpoint around September 11, after which, deformation accelerated sharply, followed by stabilization in phase 3 and a decrease in the following phases. The level of deformation suggested that a shallow magma intrusion was established. Based on the historical eruptive pattern, it is possible to infer two possible hazard-forecast scenarios: (a) the volcano could enter a prolonged phase of tranquility for more than one century or, (b) a new eruption could occur between ca. 2045 and 2065, with a slightly shorter duration than this recent one. Therefore, if the more pessimistic scenario is assumed, appropriate territorial planning is required.

Validation and Comparison of Nutrient Intakes from Two Dietary Questionnaires Developed for the Multiethnic Cohort Study - Lynne R. Wilkens; Minji Kang; Song-Yi Park; Adam Sawyer; Carol J. Boushey; Donna Lyn M. Au; Hee-Young Paik; Loïc Le Marchand; Christopher A. Haiman; Laurence N. Kolonel; Suzanne P. Murphy (Journal of the Academy of Nutrition and Dietetics, 2023)

Correction to: Mapping of a novel major effect Hessian fly field partial-resistance locus in southern soft red winter wheat line LA03136E71 - Z. J. Winn; R. Acharya; K. Merrill; J. Lyerly; G. Brown‑Guedira; S. Cambron; S. H. Harrison; D. Reisig; J. P. Murphy (Theoretical and Applied Genetics, 2023)

Use of Enrofloxacin and Hydrotherapy in the Management of Fibrodysplasia Ossificans Progressiva (FOP) in a Savannah Cat - Kim L. Jacobsen; Valerie Wiebe; Autumn P. Davidson; Brian G. Murphy; Jr. Roy R. Pool (Topics in Companion Animal Medicine, 2023)

USUAL Watershed Tools: A new geospatial toolkit for hydro-geomorphic delineation - Scott R. David; Brendan P. Murphy; Jonathan A. Czuba; Muneer Ahammad; Patrick Belmont (Environmental Modelling & Software, 2023)

Unified understanding of intrinsic and extrinsic controls of dissolved organic carbon reactivity in aquatic ecosystems - Martin Berggren; François Guillemette; Magdalena Bieroza; Ishi Buffam; Anne Deininger; Jeffrey A. Hawkes; Dolly N. Kothawala; Richard LaBrie; Jean‐François Lapierre; Kathleen R. Murphy; Enass S. Al‐Kharusi; Mayra P. D. Rulli; et al. (Ecology, 2022)
Despite our growing understanding of the global carbon cycle, scientific consensus on the drivers and mechanisms that control dissolved organic carbon (DOC) turnover in aquatic systems is lacking, hampered by the mismatch between research that approaches DOC reactivity from either intrinsic (inherent chemical properties) or extrinsic (environmental context) perspectives. Here we propose a conceptual view of DOC reactivity in which the combination of intrinsic and extrinsic factors controls turnover rates and determines which reactions will occur. We review three major types of reactions (biological, photochemical, and flocculation) from an intrinsic chemical perspective and further define the environmental features that modulate the expression of chemically inherent reactivity potential. Finally, we propose hypotheses of how extrinsic and intrinsic factors together shape patterns in DOC turnover across the land‐to‐ocean continuum, underscoring that there is no intrinsic DOC reactivity without environmental context. By acknowledging the intrinsic–extrinsic control duality, our framework intends to foster improved modeling of DOC reactivity and its impact on ecosystem services.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

2‐Aminoethylphosphonate utilization in Pseudomonas putida BIRD ‐1 is controlled by multiple master regulators - Andrew R. J. Murphy; David J. Scanlan; Yin Chen; Gary D. Bending; John P. Hammond; Elizabeth M. H. Wellington; Ian D. E. A. Lidbury (Environmental Microbiology, 2022)
Summary Bacteria possess various regulatory mechanisms to detect and coordinate a response to elemental nutrient limitation. In pseudomonads, the two‐component system regulators CbrAB, NtrBC and PhoBR, are responsible for regulating cellular response to carbon (C), nitrogen (N) and phosphorus (P) respectively. Phosphonates are reduced organophosphorus compounds produced by a broad range of biota and typified by a direct C‐P bond. Numerous pseudomonads can use the environmentally abundant phosphonate species 2‐aminoethylphosphonate (2AEP) as a source of C, N, or P, but only PhoBR has been shown to play a role in 2AEP utilization. On the other hand, utilization of 2AEP as a C and N source is considered substrate inducible. Here, using the plant‐growth‐promoting rhizobacterium Pseudomonas putida BIRD‐1 we present evidence that 2AEP utilization is under dual regulation and only occurs upon depletion of C, N, or P, controlled by CbrAB, NtrBC, or PhoBR respectively. However, the presence of 2AEP was necessary for full gene expression, i.e. expression was substrate inducible. Mutation of a LysR‐type regulator, termed AepR, upstream of the 2AEP transaminase‐phosphonatase system (PhnWX), confirmed this dual regulatory mechanism. To our knowledge, this is the first study identifying coordination between global stress response and substrate‐specific regulators in phosphonate metabolism.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Mapping of a novel major effect Hessian fly field partial-resistance locus in southern soft red winter wheat line LA03136E71 - Z. J. Winn; R. Acharya; K. Merrill; J. Lyerly; G. Brown-Guedira; S. Cambron; S. H. Harrison; D. Reisig; J. P. Murphy (Theoretical and Applied Genetics, 2021)

Disturbance type and species life history predict mammal responses to humans - Justin P. Suraci; Kaitlyn M. Gaynor; Maximilian L. Allen; Peter Alexander; Justin S. Brashares; Sara Cendejas‐Zarelli; Kevin Crooks; L. Mark Elbroch; Tavis Forrester; Austin M. Green; Jeffrey Haight; Nyeema C. Harris; et al. (Global Change Biology, 2021)
Human activity and land use change impact every landscape on Earth, driving declines in many animal species while benefiting others. Species ecological and life history traits may predict success in human‐dominated landscapes such that only species with “winning” combinations of traits will persist in disturbed environments. However, this link between species traits and successful coexistence with humans remains obscured by the complexity of anthropogenic disturbances and variability among study systems. We compiled detection data for 24 mammal species from 61 populations across North America to quantify the effects of (1) the direct presence of people and (2) the human footprint (landscape modification) on mammal occurrence and activity levels. Thirty‐three percent of mammal species exhibited a net negative response (i.e., reduced occurrence or activity) to increasing human presence and/or footprint across populations, whereas 58% of species were positively associated with increasing disturbance. However, apparent benefits of human presence and footprint tended to decrease or disappear at higher disturbance levels, indicative of thresholds in mammal species’ capacity to tolerate disturbance or exploit human‐dominated landscapes. Species ecological and life history traits were strong predictors of their responses to human footprint, with increasing footprint favoring smaller, less carnivorous, faster‐reproducing species. The positive and negative effects of human presence were distributed more randomly with respect to species trait values, with apparent winners and losers across a range of body sizes and dietary guilds. Differential responses by some species to human presence and human footprint highlight the importance of considering these two forms of human disturbance separately when estimating anthropogenic impacts on wildlife. Our approach provides insights into the complex mechanisms through which human activities shape mammal communities globally, revealing the drivers of the loss of larger predators in human‐modified landscapes.

Argo Data 1999–2019: Two Million Temperature-Salinity Profiles and Subsurface Velocity Observations From a Global Array of Profiling Floats - Annie P. S. Wong; Susan E. Wijffels; Stephen C. Riser; Sylvie Pouliquen; Shigeki Hosoda; Dean Roemmich; John Gilson; Gregory C. Johnson; Kim Martini; David J. Murphy; Megan Scanderbeg; T. V. S. Udaya Bhaskar; et al. (Frontiers in Marine Science, 2020)

Effect of Shallow Slip Amplification Uncertainty on Probabilistic Tsunami Hazard Analysis in Subduction Zones: Use of Long-Term Balanced Stochastic Slip Models - A. Scala; S. Lorito; F. Romano; S. Murphy; J. Selva; R. Basili; A. Babeyko; A. Herrero; A. Hoechner; F. Løvholt; F. E. Maesano; P. Perfetti; et al. (Pure and Applied Geophysics, 2020)

Perspectives on in situ Sensors for Ocean Acidification Research - Akash R. Sastri; James R. Christian; Eric P. Achterberg; Dariia Atamanchuk; Justin J. H. Buck; Philip Bresnahan; Patrick J. Duke; Wiley Evans; Stephen F. Gonski; Bruce Johnson; S. Kim Juniper; Steve Mihaly; et al. (Frontiers in Marine Science, 2019)

Toward the Integrated Marine Debris Observing System - Nikolai Maximenko; Paolo Corradi; Kara Lavender Law; Erik Van Sebille; Shungudzemwoyo P. Garaba; Richard Stephen Lampitt; Francois Galgani; Victor Martinez-Vicente; Lonneke Goddijn-Murphy; Joana Mira Veiga; Richard C. Thompson; Christophe Maes; et al. (Frontiers in Marine Science, 2019)

Changes in local free-living parasite populations in response to cleaner manipulation over 12 years - A. S. Grutter; S. P. Blomberg; S. Box; R. Bshary; O. Ho; E. M. P. Madin; E. C. McClure; M. G. Meekan; J. M. Murphy; M. A. Richardson; P. C. Sikkel; C. A. Sims; et al. (Oecologia, 2019)

Outlier SNPs detect weak regional structure against a background of genetic homogeneity in the Eastern Rock Lobster, Sagmariasus verreauxi - Laura N. Woodings; Nicholas P. Murphy; Stephen R. Doyle; Nathan E. Hall; Andrew J. Robinson; Geoffrey W. Liggins; Bridget S. Green; Ira R. Cooke; James J. Bell; Jan M. Strugnell (Marine Biology, 2018)

Field of View Normalization in Multi-Site Brain MRI - Yangming Ou; Lilla Zöllei; Xiao Da; Kallirroi Retzepi; Shawn N. Murphy; Elizabeth R. Gerstner; Bruce R. Rosen; P. Ellen Grant; Jayashree Kalpathy-Cramer; Randy L. Gollub (Neuroinformatics, 2018)

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Mother–infant interactions and regional brain volumes in infancy: an MRI study - Vaheshta Sethna; Inês Pote; Siying Wang; Maria Gudbrandsen; Anna Blasi; Caroline McCusker; Eileen Daly; Emily Perry; Kerrie P. H. Adams; Maria Kuklisova-Murgasova; Paula Busuulwa; Sarah Lloyd-Fox; et al. (Brain Structure and Function, 2017)

Evaluation of the BioFire FilmArray® GastrointestinalPanel in a Midwestern Academic Hospital - C. N. Murphy; R. C. Fowler; P. C. Iwen; P. D. Fey (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

Savanna woody encroachment is widespread across three continents - Nicola Stevens; Caroline E. R. Lehmann; Brett P. Murphy; Giselda Durigan (Global Change Biology, 2017)
Tropical savannas are a globally extensive biome prone to rapid vegetation change in response to changing environmental conditions. Via a meta‐analysis, we quantified savanna woody vegetation change spanning the last century. We found a global trend of woody encroachment that was established prior the 1980s. However, there is critical regional variation in the magnitude of encroachment. Woody cover is increasing most rapidly in the remaining uncleared savannas of South America, most likely due to fire suppression and land fragmentation. In contrast, Australia has experienced low rates of encroachment. When accounting for land use, African savannas have a mean rate annual woody cover increase two and a half times that of Australian savannas. In Africa, encroachment occurs across multiple land uses and is accelerating over time. In Africa and Australia, rising atmospheric CO 2 , changing land management and rainfall are likely causes. We argue that the functional traits of each woody flora, specifically the N‐fixing ability and architecture of woody plants, are critical to predicting encroachment over the next century and that African savannas are at high risk of widespread vegetation change.

Outlier SNPs enable food traceability of the southern rock lobster, Jasus edwardsii - Cecilia Villacorta-Rath; Irina Ilyushkina; Jan M. Strugnell; Bridget S. Green; Nicholas P. Murphy; Stephen R. Doyle; Nathan E. Hall; Andrew J. Robinson; James J. Bell (Marine Biology, 2016)

Comparative genomic, proteomic and exoproteomic analyses of three Pseudomonas strains reveals novel insights into the phosphorus scavenging capabilities of soil bacteria - Ian D. E. A. Lidbury; Andrew R. J. Murphy; David J. Scanlan; Gary D. Bending; Alexandra M. E. Jones; Jonathan D. Moore; Andrew Goodall; John P. Hammond; Elizabeth M. H. Wellington (Environmental Microbiology, 2016)
Summary Bacteria that inhabit the rhizosphere of agricultural crops can have a beneficial effect on crop growth. One such mechanism is the microbial‐driven solubilization and remineralization of complex forms of phosphorus (P). It is known that bacteria secrete various phosphatases in response to low P conditions. However, our understanding of their global proteomic response to P stress is limited. Here, exoproteomic analysis of Pseudomonas putida BIRD‐1 (BIRD‐1), Pseudomonas fluorescens SBW25 and Pseudomonas stutzeri DSM4166 was performed in unison with whole‐cell proteomic analysis of BIRD‐1 grown under phosphate (Pi) replete and Pi deplete conditions. Comparative exoproteomics revealed marked heterogeneity in the exoproteomes of each Pseudomonas strain in response to Pi depletion. In addition to well‐characterized members of the PHO regulon such as alkaline phosphatases, several proteins, previously not associated with the response to Pi depletion, were also identified. These included putative nucleases, phosphotriesterases, putative phosphonate transporters and outer membrane proteins. Moreover, in BIRD‐1, mutagenesis of the master regulator, phoBR , led us to confirm the addition of several novel PHO‐dependent proteins. Our data expands knowledge of the Pseudomonas PHO regulon, including species that are frequently used as bioinoculants, opening up the potential for more efficient and complete use of soil complexed P.

Controls over Ocean Mesopelagic Interior Carbon Storage (COMICS): Fieldwork, Synthesis, and Modeling Efforts - Richard J. Sanders; Stephanie A. Henson; Adrian P. Martin; Tom R. Anderson; Raffaele Bernardello; Peter Enderlein; Sophie Fielding; Sarah L. C. Giering; Manuela Hartmann; Morten Iversen; Samar Khatiwala; Phyllis Lam; et al. (Frontiers in Marine Science, 2016)

Climate change and Southern Ocean ecosystems I: how changes in physical habitats directly affect marine biota - Andrew J. Constable; Jessica Melbourne‐Thomas; Stuart P. Corney; Kevin R. Arrigo; Christophe Barbraud; David K. A. Barnes; Nathaniel L. Bindoff; Philip W. Boyd; Angelika Brandt; Daniel P. Costa; Andrew T. Davidson; Hugh W. Ducklow; et al. (Global Change Biology, 2014)
Antarctic and Southern Ocean ( ASO ) marine ecosystems have been changing for at least the last 30 years, including in response to increasing ocean temperatures and changes in the extent and seasonality of sea ice; the magnitude and direction of these changes differ between regions around Antarctica that could see populations of the same species changing differently in different regions. This article reviews current and expected changes in ASO physical habitats in response to climate change. It then reviews how these changes may impact the autecology of marine biota of this polar region: microbes, zooplankton, salps, Antarctic krill, fish, cephalopods, marine mammals, seabirds, and benthos. The general prognosis for ASO marine habitats is for an overall warming and freshening, strengthening of westerly winds, with a potential pole‐ward movement of those winds and the frontal systems, and an increase in ocean eddy activity. Many habitat parameters will have regionally specific changes, particularly relating to sea ice characteristics and seasonal dynamics. Lower trophic levels are expected to move south as the ocean conditions in which they are currently found move pole‐ward. For Antarctic krill and finfish, the latitudinal breadth of their range will depend on their tolerance of warming oceans and changes to productivity. Ocean acidification is a concern not only for calcifying organisms but also for crustaceans such as Antarctic krill; it is also likely to be the most important change in benthic habitats over the coming century. For marine mammals and birds, the expected changes primarily relate to their flexibility in moving to alternative locations for food and the energetic cost of longer or more complex foraging trips for those that are bound to breeding colonies. Few species are sufficiently well studied to make comprehensive species‐specific vulnerability assessments possible. Priorities for future work are discussed.

Fire regimes and woody biomass dynamics in Australian savannas - Brett P. Murphy; Caroline E. R. Lehmann; Jeremy Russell‐Smith; Michael J. Lawes (Journal of Biogeography, 2014)
Aim Many tropical savannas are undergoing a trend of increasing woody biomass, or ‘woody thickening’. Management to reduce fire frequency and intensity in savannas could substantially increase the amount of carbon stored in woody biomass. We addressed two questions: (1) are northern Australian savannas thickening; and (2) to what extent, and by what demographic processes, does fire affect woody biomass accumulation? Location Three large national parks, covering 24,000 km 2 , in monsoonal northern Australia. Methods We examined changes in woody biomass carbon stocks – inferred from tree basal area and the density of woody understorey plants – over a 10‐year period in 136 savanna monitoring plots. We statistically assessed these changes in relation to fire frequency and severity. We used a meta‐analysis to identify general trends in woody cover in Australian savannas over the last half‐century. Results Woody biomass carbon stocks were relatively stable across the three national parks, but rates of change were statistically indistinguishable from earlier findings of a weak thickening trend. Change was negatively correlated with fire frequency, particularly the frequency of severe fires. High frequencies of severe fires decreased rates of accumulation of biomass by existing trees (through reductions in tree growth and death of individual stems), rather than whole‐tree mortality and suppression of recruitment. However, across northern Australia, our meta‐analysis identified a general, albeit weak, trend of woody thickening. Main conclusions The drivers of northern Australia's weak thickening trend are uncertain, but likely candidates include increasing atmospheric CO 2 concentration and water availability, and pastoral intensification. We demonstrate that changes to fire management have the potential to either increase or decrease rates of woody thickening relative to any underlying trend. Understanding how savanna fires affect woody biomass, and how fire effects are mediated by climate and CO 2 , are essential research priorities to predict the fate of savannas.

Molecular cloning of the trypsin inhibitor from the skin secretion of the Madagascan Tomato Frog, Dyscophus guineti (Microhylidae), and insights into its potential defensive role - Enrico König; Christina Wesse; Anna C. Murphy; Mei Zhou; Lei Wang; Tianbao Chen; Chris Shaw; Olaf R. P. Bininda-Emonds (Organisms Diversity & Evolution, 2013)

Evaluation of real-time flash flood forecasts for Haiti during the passage of Hurricane Tomas, November 4–6, 2010 - E. Shamir; K. P. Georgakakos; C. Spencer; T. M. Modrick; M. J. Murphy; R. Jubach (Natural Hazards, 2013)

A Strategy for Prioritizing Threats and Recovery Actions for At-Risk Species - Catherine R. Darst; Philip J. Murphy; Nathan W. Strout; Steven P. Campbell; Kimberleigh J. Field; Linda Allison; Roy C. Averill-Murray (Environmental Management, 2013)

Estimating rates of biologically driven coral reef framework production and erosion: a new census-based carbonate budget methodology and applications to the reefs of Bonaire - C. T. Perry; E. N. Edinger; P. S. Kench; G. N. Murphy; S. G. Smithers; R. S. Steneck; P. J. Mumby (Coral Reefs, 2012)

Association of cord blood methylation fractions at imprinted insulin-like growth factor 2 (IGF2), plasma IGF2, and birth weight - Cathrine Hoyo; Kimberly Fortner; Amy P. Murtha; Joellen M. Schildkraut; Adelheid Soubry; Wendy Demark-Wahnefried; Randy L. Jirtle; Joanne Kurtzberg; Michele R. Forman; Francine Overcash; Zhiqing Huang; Susan K. Murphy (Cancer Causes & Control, 2012)

Impulsive behaviour induced by both NMDA receptor antagonism and GABAA receptor activation in rat ventromedial prefrontal cortex - Emily R. Murphy; Anushka B. P. Fernando; Gonzalo P. Urcelay; Emma S. J. Robinson; Adam C. Mar; David E. H. Theobald; Jeffrey W. Dalley; Trevor W. Robbins (Psychopharmacology, 2012)

Long-Term Trends in Chesapeake Bay Seasonal Hypoxia, Stratification, and Nutrient Loading - Rebecca R. Murphy; W. Michael Kemp; William P. Ball (Estuaries and Coasts, 2011)

4-(4-Chloro-2-methylphenoxy)-N-hydroxybutanamide (CMH) targets mRNA of the c-FLIP variants and induces apoptosis in MCF-7 human breast cancer cells - Khadijeh Bijangi-Vishehsaraei; Mohammad Reza Saadatzadeh; Su Huang; Michael P. Murphy; Ahmad R. Safa (Molecular and Cellular Biochemistry, 2010)

Using carbon isotope analysis of the diet of two introduced Australian megaherbivores to understand Pleistocene megafaunal extinctions - David M. J. S. Bowman; Brett P. Murphy; Clive R. McMahon (Journal of Biogeography, 2010)
Aim Australia lost a diverse assemblage of large marsupial herbivores in the late Pleistocene, with suggestions that the extinctions were biased towards browsers. In modern times two bovines, the Asian water buffalo ( Bubalus bubalis ) and banteng ( Bos javanicus ), have established feral populations in the Northern Territory, Australia. Buffalo have aggressively expanded throughout the savanna landscape, yet banteng remain near their point of introduction on the Cobourg Peninsula. We hypothesized that this difference is related to feeding ecology, possibly reflecting a legacy of the Pleistocene extinctions. Location Western Arnhem Land, Northern Territory, Australia. Methods Analysing a previously published dataset of body mass and feeding ecology of extinct and extant marsupial herbivores, we evaluated whether browsers were at greater risk of extinction than grazers. We compared the carbon isotope composition and nitrogen content of banteng and buffalo dung in order to evaluate the hypotheses that the differences in invasion success are related to feeding ecology, and that seasonal variation in browse consumption is linked to changing nutritional quality of grass. Results Controlling for body mass, the Pleistocene extinctions were clearly biased towards browsers. Introduced banteng appear to be primarily browsers, with their diets comprising 40% grass in the wet season and 15% in the late dry season. Buffalo have a more variable diet, with an increasing proportion of browse from the wet (30%) to the late dry season (75%), and can therefore be described as switching from grazer to browser. The decline of grass in the diet of both species appears to reflect the decline in the nutritional value of grass through the dry season, an inference supported by the negative relationship between δ 13 C values and the nitrogen content of dung. Main conclusions Banteng and buffalo are much larger than extant native herbivores, of which browsers are restricted to isolated rocky habitats. This suggests that banteng and buffalo have filled niches made vacant following the Pleistocene extinctions. The success of buffalo appears to be related to their greater dietary breadth, which enables them to graze and browse in eucalypt savannas, whilst the browsing banteng remain tethered to a mosaic of rain forest patches. The restriction of browsers may be a long‐range consequence of habitat transformations associated with Aboriginal landscape burning.

Environmental predictors of the occurrence of exotic Hydrilla verticillata (L.f.) Royle and native Egeria najas Planch. in a sub-tropical river floodplain: the Upper River Paraná, Brazil - W. T. Z. Sousa; S. M. Thomaz; K. J. Murphy; M. J. Silveira; R. P. Mormul (Hydrobiologia, 2009)

Circulating fatty acids and prostate cancer risk in a nested case–control study: the Multiethnic Cohort - Song-Yi Park; Lynne R. Wilkens; Susanne M. Henning; Loïc Le Marchand; Kun Gao; Marc T. Goodman; Suzanne P. Murphy; Brian E. Henderson; Laurence N. Kolonel (Cancer Causes & Control, 2009)

Bioengineering and Imaging Research Opportunities Workshop V: A Summary - William R. Hendee; Kevin Cleary; Richard L. Ehman; Gary D. Fullerton; Warren S. Grundfest; John Haller; Christine Kelley; Anne E. Meyer; Robert F. Murphy; William Phillips; Vladimir P. Torchilin (Annals of Biomedical Engineering, 2008)

Dietary fiber and colorectal cancer risk: the multiethnic cohort study - Abraham M. Y. Nomura; Jean H. Hankin; Brian E. Henderson; Lynne R. Wilkens; Suzanne P. Murphy; Malcolm C. Pike; Loic Le Marchand; Daniel O. Stram; Kristine R. Monroe; Laurence N. Kolonel (Cancer Causes & Control, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Occurrence of Cryptosporidium parvum and Bacterial Pathogens in Faecal Material in the Red Fox (Vulpes vulpes) Population - Y. Nagano; M. B. Finn; C. J. Lowery; T. Murphy; J. Moriarty; E. Power; D. Toolan; A. O’Loughlin; M. Watabe; K. A. McCorry; E. Crothers; J. S. G. Dooley; et al. (Veterinary Research Communications, 2007)

Body mass index and physical activity as risk factors for pancreatic cancer: the Multiethnic Cohort Study - Ute Nöthlings; Lynne R. Wilkens; Suzanne P. Murphy; Jean H. Hankin; Brian E. Henderson; Laurence N. Kolonel (Cancer Causes & Control, 2007)

Sediment TCDD-EQs and EROD and MROD Activities in Ranid Frogs from Agricultural and Nonagricultural Sites in Michigan (USA) - M. B. Murphy; M. Hecker; K. K. Coady; A. R. Tompsett; P. D. Jones; J. L. Newsted; H. L. Wong; L. H. du Preez; K. R. Solomon; J. A. Carr; E. E. Smith; R. J. Kendall; et al. (Archives of Environmental Contamination and Toxicology, 2006)

Gene expression analysis in a canine model of X-linked Alport syndrome - Kimberly A. Greer; Marnie A. Higgins; Melissa L. Cox; Timothy P. Ryan; Brian R. Berridge; Clifford E. Kashtan; George E. Lees; Keith E. Murphy (Mammalian Genome, 2006)

Evidence of an oscillating peripheral clock in an equine fibroblast cell line and adipose tissue but not in peripheral blood - Barbara A. Murphy; Mandi M. Vick; Dawn R. Sessions; R. Frank Cook; Barry P. Fitzgerald (Journal of Comparative Physiology A, 2006)

Using Indicator Species to Predict Species Richness of Multiple Taxonomic Groups - ERICA FLEISHMAN; JAMES R. THOMSON; RALPH MAC NALLY; DENNIS D. MURPHY; JOHN P. FAY (Conservation Biology, 2005)
Values of species richness are used widely to establish conservation and management priorities. Because inventory data, money, and time are limited, use of surrogates such as “indicator” species to estimate species richness has become common. Identifying sets of indicator species that might reliably predict species richness, especially across taxonomic groups, remains a considerable challenge. We used genetic algorithms and a Bayesian approach to explain individual and combined species richness of two taxonomic groups as a function of occurrence patterns of indicator species drawn from either both groups or one group. Genetic algorithms iteratively screen large numbers of potential models and predictor variables in a process that emulates natural selection. The best‐fitting models of bird species richness and butterfly species richness explained approximately 80% of deviances and included only indicator species from the same taxonomic group. Using species from both taxonomic groups as potential predictors did not improve model fit but slightly improved the parsimony (fewer predictors) of the model of bird species richness. The best model of combined species richness included five butterflies and one bird and explained 83% of deviance, whereas a model of combined species richness based on six butterflies as indicators explained 82% of deviance. A model of combined species richness based on birds alone explained 72% of deviance. We found that a small, common set of species could be used to predict separately the species richness of multiple taxonomic groups. We built models explaining approximately 70% of the deviance in species richness of birds and butterflies based on a common set of three bird species and three butterfly species. We also identified a set of six species of butterflies that predicted ≥66% of both bird species richness and butterfly species richness. Our approach is applicable to any assemblage or ecosystem, and may be useful both for estimating species richness and for gaining insight into mechanisms that influence diversity patterns.

Impact of the European Antimicrobial Resistance Surveillance System on the development of a national programme to monitor resistance in Staphylococcus aureus and Streptococcus pneumoniae in Ireland, 1999–2003 - O. M. Murphy; S. Murchan; D. Whyte; H. Humphreys; A. Rossney; P. Clarke; R. Cunney; C. Keane; L. E. Fenelon; D. O’Flanagan (European Journal of Clinical Microbiology & Infectious Diseases, 2005)

Environmental Consequences of Intensively Managed Forest Plantations in the Pacific Northwest - John P. Hayes; Stephen H. Schoenholtz; Mitschka J. Hartley; Glen Murphy; Robert F. Powers; Dean Berg; Steven R. Radosevich (Journal of Forestry, 2005)
Environmental consequences of intensively managed forest plantations (IMFP) are manifested primarily through influences on biodiversity, soils, and water resources. These consequences may be positive, neutral, or negative, depending on the spatial and temporal context and site-specificdetails. Many aspects of environmental consequences of IMFPs are increasingly understood, but significant gaps in our knowledge remain. Societal environmental goals and objectives of IMFPs remain poorly articulated and fuel a lively, often heated, social dialogue that will likely continuefor some time to come.

Modeling Sustainability of Arctic Communities: An Interdisciplinary Collaboration of Researchers and Local Knowledge Holders - Jack A. Kruse; Robert G. White; Howard E. Epstein; Billy Archie; Matt Berman; Stephen R. Braund; F. Stuart Chapin; Johnny Charlie; Colin J. Daniel; Joan Eamer; Nick Flanders; Brad Griffith; et al. (Ecosystems, 2004)

Cytokine gene polymorphisms in ischaemic heart disease: investigation using family-based tests of association - Paul G. McGlinchey; Mark S. Spence; Chris C. Patterson; Adrian R. Allen; Gillian Murphy; David A. Savage; A. Peter Maxwell; Pascal P. McKeown (Journal of Molecular Medicine, 2004)

Sequence Analysis of the Washington/1964 strain of Human Parainfluenza Virus Type 1 (HPIV1) and Recovery and Characterization of Wild Type Recombinant HPIV1 Produced by Reverse Genetics - J. T. Newman; S. R. Surman; J. M. Riggs; Chris T. Hansen; P. L. Collins; B. R. Murphy; M.H. Skiadopoulos (Virus Genes, 2003)

Development of Multiplexed Fluorescence Microbead Covalent Assays (FMCAs) for Pesticide Biomonitoring - R. E. Biagini; D. M. Murphy; D. L. Sammons; J. P. Smith; C. A. F. Striley; B. A. MacKenzie (Bulletin of Environmental Contamination and Toxicology, 2002)

Prediction of uphill time-trial bicycling performance in humans with a scaling-derived protocol - D. P. Heil; O. F. Murphy; A. R. Mattingly; B. K. Higginson (European Journal of Applied Physiology, 2001)

Phytoplankton distributions around New Zealand derived from SeaWiFS remotely‐sensed ocean colour data - R. J. Murphy; M. H. Pinkerton; K. M. Richardson; J. M. Bradford‐Grieve; P. W. Boyd (New Zealand Journal of Marine and Freshwater Research, 2001)
Ocean colour data from the NASA Sea‐viewing Wide Field‐of‐view Sensor (SeaWiFS) was used to estimate chlorophyll a concentration around New Zealand on a monthly basis between September 1997 and May 2000. The performance of the SeaWiFS chlorophyll a algorithm (OC4v4) was investigated by comparing in situ measurements of the underwater light field with measurements of phytoplankton pigment concentration by High Performance Liquid Chromatography. The algorithm performed well for chlorophyll a concentrations below 0.6 mg m‐3 but overestimated by a factor of two or more at higher concentrations. The average chlorophyll a concentration for New Zealand Exclusive Economic Zone was calculated as an indication of the overall productivity of the region and varied between 0.26 and 0.43 mg m‐3 with no obvious relationship to the Southern Oscillation Index. New Zealand northern subtropical and Tasman Sea waters had a classical cycle of spring and autumn chlorophyll blooms consistent with production being co‐limited by nitrate and light. Subantarctic waters had a low‐magnitude annual cycle of chlorophyll abundance that peaked in early autumn, consistent with production being predominantly limited by a combination of iron and light. Chlorophyll was generally highest in the Subtropical Front where subtropical and subantarctic waters mix. A series of persistent warm‐core eddies along New Zealand's east coast was obvious in many images, manifest as regions of low chlorophyll concentration.

Effective Planning and Implementation of Ecological Rehabilitation Projects: A Case Study of the Regional Municipality of Waterloo (Ontario, Canada) - LARRY R. G. MARTIN; STEPHEN D. MURPHY; SOONYA P. Quon (Environmental Management, 2001)

Sexual size dimorphism in fallow deer (Dama dama): do larger, heavier males gain greater mating success? - Alan G. McElligott; Martin P. Gammell; Hilda C. Harty; Dean R. Paini; Desmond T. Murphy; James T. Walsh; Thomas J. Hayden (Behavioral Ecology and Sociobiology, 2001)

Measurement of Serum Antigen Concentration by Ultrasound-Enhanced Immunoassay and Correlation with Clinical Outcome in Meningococcal Disease - M. A. Sobanski; R. A. Barnes; S. J. Gray; A. D. Carr; E. B. Kaczmarski; A. O'Rourke; K. Murphy; M. Cafferkey; R. W. Ellis; K. Pidcock; P. Hawtin; W. T. Coakley (European Journal of Clinical Microbiology & Infectious Diseases, 2000)

Microsatellite markers for investigating population structure in Octopus vulgaris (Mollusca: Cephalopoda) - E. C. Greatorex; C. S. Jones; J. Murphy; L. N. Key; A. M. Emery; P. R. Boyle (Molecular Ecology, 2000)

Soluble organic nitrogen in agricultural soils - D. V. Murphy; A. J. Macdonald; E. A. Stockdale; K. W. T. Goulding; S. Fortune; J. L. Gaunt; P. R. Poulton; J. A. Wakefield; C. P. Webster; W. S. Wilmer (Biology and Fertility of Soils, 2000)

Combined analysis of field and model data: A case study of the phosphate dynamics in the German Bight in summer 1994 - Th. Pohlmann; Th. Raabe; R. Doerffer; S. Beddig; U. Brockmann; S. Dick; M. Engel; K. -J. Hesse; P. König; B. Mayer; A. Moll; D. Murphy; et al. (Ocean Dynamics, 1999)

SPM concentrations in the German Bight: comparison between a model simulation and measurements - W. Puls; J. Beusekom; U. Brockmann; R. Doerffer; U. Hentschke; P. König; D. Murphy; B. Mayer; A. Müller; Th. Pohlmann; A. Reimer; R. Schmidt-Nia; et al. (Ocean Dynamics, 1999)

Chemical Ozone Loss in the Arctic Winter 1994/95 as Determined by the Match Technique - M. Rex; P. Von Der Gathen; G.O. Braathen; N.R.P. Harris; E. Reimer; A. Beck; R. Alfier; R. Krüger-carstensen; M. Chipperfield; H. De Backer; D. Balis; F. O'Connor; et al. (Journal of Atmospheric Chemistry, 1999)

Abstracts of papers presented at an international workshop on management of soilborne pathogens sponsored by the United States-Israel binational agricultural research and development fund (bard) - R. J. Cook; J. Katan; I. Chet; J. Katan; R. Rodriguez-Kabana; C. R. Taylor; J. W. Kloepper; M. M. Satour; G. L. Lazarovits; K. L. Conn; M. Tenuta; G. Kritzman; et al. (Phytoparasitica, 1998)

A Study of Ozone Laminae Using Diabatic Trajectories, Contour Advection and Photochemical Trajectory Model Simulations. - S. J. Reid; M. Rex; P. Von Der Gathen; I. Fløisand; F. Stordal; G. D. Carver; A. Beck; E. Reimer; R. Krüger-Carstensen; L. L. De Haan; G. Braathen; V. Dorokhov; et al. (Journal of Atmospheric Chemistry, 1998)

Independent Scientific Review in Natural Resource Management - Gary K. Meffe; P. Dee Boersma; Dennis D. Murphy; Barry R. Noon; H. Ronald Pulliam; Michael E. Soulé; Donald M. Waller (Conservation Biology, 1998)

SUMMER MOISTURE AVAILABILITY OVER EUROPE IN THE HADLEY CENTRE GENERAL CIRCULATION MODEL BASED ON THE PALMER DROUGHT SEVERITY INDEX - P. D. JONES; M. HULME; K. R. BRIFFA; C. G. JONES; J. F. B. MITCHELL; J. M. MURPHY (International Journal of Climatology, 1996)

Electron microscopic and antigenic studies of uncharacterized viruses. II. Evidence suggesting the placement of viruses in the familyBunyaviridae - H. G. Zeller; N. Karabatsos; Ch. H. Calisher; J. -P. Digoutte; C. B. Cropp; F. A. Murphy; R. E. Shope (Archives of Virology, 1989)

Electron microscopy and antigenic studies of uncharacterized viruses. I. Evidence suggesting the placement of viruses in familiesArenaviridae, Paramyxoviridae, orPoxviridae - H. G. Zeller; N. Karabatsos; Ch. H. Calisher; J. -P. Digoutte; F. A. Murphy; R. E. Shope (Archives of Virology, 1989)

Electron microscopic and antigenic studies of uncharacterized viruses. III. Evidence suggesting the placement of viruses in the familyReoviridae - H. G. Zeller; N. Karabatsos; C. H. Calisher; J. -P. Digoutte; C. B. Cropp; F. A. Murphy; R. E. Shope (Archives of Virology, 1989)

Temperature-sensitive mutants of influenza A virus: Evaluation of the Alaska/77-ts-1 A 2 temperature-sensitive recombinant virus in seronegative adult volunteers - B. R. Murphy; R. M. Chanock; R. G. Douglas; R. F. Betts; D. H. Waterman; H. P. Holley; D. L. Hoover; S. Suwanagool; D. R. Nalin; M. M. Levine (Archives of Virology, 1980)

Cold adapted variants of influenza A - S. B. Spring; H. F. Maassab; A. P. Kendal; B. R. Murphy; R. M. Chanock (Archives of Virology, 1977)

s 60th annual meeting The Potato Association of America - R. Kunkel; N. M. Holstad; R. E. Thornton; J. C. Bishop; Herman Timm; V. C. Shekhar; W. M. Iritani; Thornton Robert; Gary Hyde; Malamud Oscar; Robert B. O’Keefe; Mccown Brent; et al. (American Journal of Potato Research, 1976)

s of papers presented at the Fifty-Second Annual Meeting of The Potato Association of America - J. A. Crozier; P. J. Ito; Puente De La Fermin; S. J. Peloquin; P. Severino; E. C. Doll; D. R. Christenson; A. R. Wolcott; Hawkins Arthur; F. D. Howard; Herman Timm; W. J. Flocker; et al. (American Journal of Potato Research, 1968)

s of papers presented at the Forty-Third annual meeting of The Potato Association of America - R. H. Bagnall; D. A. Young; Barrel R. Bienz; G. D. Brill; J. C. Campbell; G. R. Blake; Paul N. Carpenter; George O. Estes; Harold W. Gausman; Harold W. Gausman; Hawkins Arthur; Henning P. Hansen; et al. (American Journal of Potato Research, 1959)

s of papers presented at the Forty-First annual meeting - Jay L. Haddock; Ray D. Jackson; W. O. Harrington; R. L. Olson; W. J. Weston; Mary L. Belote; W. J. Hooker; A. P. Benson; R. W. Hougas; S. J. Poloquin; R. W. Ross; G. V. C. Houghland; et al. (American Journal of Potato Research, 1958)